НОВІ ЗНАХІДКИ CERCERIS TUBERCULATA (VILLERS, 1787) (HYMENOPTERA: CRABRONIDAE) У МЕЖАХ УКРАЇНИ, ІЗ ДАНИМИ ЩОДО ПАРАЗИТОЇДІВ ТА ЗДОБИЧІ - Martynova, K. V.; Martynov, A. V. (public organization "Ukrainian Entomological Society", I.I. Schmalhausen Institute of Zoology of National Academy of Sciences of Ukraine, Institute of Plant Protection of National Academy of Agrarian Sciences of Ukraine, 2021)
Present paper reports observations on the digger wasp Cerceris tuberculata (Villers, 1787) (Hymenoptera: Crabronidae), listed in Red Data Book of Ukraine, its parasitoids and prey. The observations revealed two parasitoids associated with this wasp: a cuckoo wasp Hedychrum virens Dahlbom, 1845 (Chrysididae) and velvet ant Nemka viduata viduata (Pallas, 1773) (Mutillidae). The host-parasitoid association of this velvet ant and C. tuberculata is provided for the first time. Four species of weevils were registered as a prey of C. tuberculata, three of them are given for the first time herein. New records of the species from Zaporizhzhya and Kherson Regions are provided; the species is reported from Zaporizhzhia Region for the first time.